Legal Tech and the New Sharing Economy - Corrales Compagnucci, Marcelo; Forgó, Nikolaus; Kono, Toshiyuki; Teramoto, Shinto; Vermeulen, Erik P.M (Perspectives in Law, Business and Innovation, 2020)
XVI, 257 p. 43 illus., 40 illus. in color.